Vsadni kardioverter-defibrilator pri atrio-biventrikularni elektrostimulaciji srca - Vokač, Damijan (Zdravniški vestnik, 2005)
Background. Patients with advanced heart failure bears bad prognosis, despite modern medical treatment year mortality rate spans from 30 up to 70 %. Besides terminal heart failure the second most frequent cause is sudden death due to ventricular tachyarrhythmias as ventricular tachycardia and fibrillation. Ventricular fibrillation is very frequent cause of mortality of terminal heart failure especially in ischemic subgroup. Clinical studies have presented improvement of heart function by use of biventricular stimulation of patients with advanced heart failure and intraventricular conduction defects as left bundle branch block. Method very successfully improves acute hemodynamic parameters due to resynchronization of septal and lateral wall of left ventricle and improves economy of the heart contraction. Although these effects are present immediately after implantation they persist also through longer period. Method improves quality of life and also decreases mortality rate proved by clinical studies. Despite successful therapy mortality rate due to sudden death remains high. Implantable cardioverters defibrillators successfully prevent sudden cardiac death due to ventricular tachyarrhythmia. They are successful due to straightforward recognition of ventricular tachycardia or fibrillation and immediate electrical schock delivery. Cardiovertes defibrillators are successful in prevention of sudden cardiac death but they do not improve quality of life of heart failure patients like resynchronization therapy. Thus, combined therapy resynchronization and cardioverter defibrillator as a single implantable device has been developed. Conclusions. Due to very successful combined therapy the application of biventricular cardioverters defibrillators into clinical practice has increased. Implantation of biventricular cardioverter defibrillator is complex but very successful procedure. It is economically acceptable when proper indication has been stated. Large multicentric randomized clinical trials have proved better quality of life and reduced mortality rate in advanced heart failure patients especially when combined with cardioverter defibrillators.
Keywords: Defibrilatorji, implantabilni; Defibrillators, implantable; Heart failure, congestive; Mortality; Odpoved srca, kongestivna; Pacemaker; Smrtnost; Srčni spodbujevalnik